Linguistic Intelligence Development Strategy Through Student Activities: A Case Study in Intensive Arabic Language Learning - Muhammad Farih; Farid Qomaruddin; Ali Ridho Saleh Mulachela; Umar Al Faruq (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2024)
This research aimed to reveal the efforts, promotion, and development of the teaching of the Arabic language in the intensive Arabic language teaching at Maulana Malik Ibrahim State Islamic University Malang to improve the linguistic intelligence of students through the student activities of the “Arabic Camp” (Mukhoyyam Arabi). The method used in this research is a case study to describe the various events that occurred in this field, which is the teaching of the Arabic language presented by lecturers of the intensive program for teaching the Arabic language to improve verbal linguistic intelligence. The research focused on the two advanced levels, which were FJ-3 and FJ-4. Among the results of this research were that the students’ activities towards the first-place competition, Arabic songs, and Arabic encouraging chants (yel-yel) programmed in the outdoor classroom in the natural environment improved verbal-linguistic intelligence toward using correct and effective words and forming sentences according to grammatical rules aimed at communication.